2020
DOI: 10.1097/cce.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Acuity of Organ Failure and Predictive Validity of Sepsis-3 Criteria

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…In our cohort, SOFA Acute greater than or equal to 2 also was associated with increased mortality. Mortality was low in the cohort analyzed by Gadrey et al ( 5 ), that is, pretest probability was lower than in our cohort. Consequently, following Fagan’s nomogram, the apparent performance of the SOFA score is worse, despite similar likelihood ratios.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In our cohort, SOFA Acute greater than or equal to 2 also was associated with increased mortality. Mortality was low in the cohort analyzed by Gadrey et al ( 5 ), that is, pretest probability was lower than in our cohort. Consequently, following Fagan’s nomogram, the apparent performance of the SOFA score is worse, despite similar likelihood ratios.…”
Section: Discussioncontrasting
confidence: 70%
“…By using SOFA not adjusted for chronic organ failures, the prognostic value of the sepsis definition may have been exaggerated in the large epidemiological studies where the differentiation between acute and chronic organ failures could not be made. In assessing mortality in patients with SOFA greater than or equal to 2 either due to total SOFA or acute SOFA only, Gadrey et al ( 5 ) found that only the prior was significantly associated with increased mortality. In our cohort, SOFA Acute greater than or equal to 2 also was associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As SOFA was designed for critical care it was anticipated that there would be a significant number of missing values for the respiratory component which requires an arterial blood gas to calculate the PaO 2 /FiO 2 ratio. There are several available alternatives for ward patients [ 27 , 28 ] which use combinations of inspired oxygen and oxygen saturations. We used Valik et al’s [ 29 ] method which allocates a SOFA score of 1 for oxygen saturations of 91–94% and 2 for oxygen saturations of less than 91% as a replacement for the missing data because it performed better than either the original SOFA scoring [ 9 ] or Gadrey et al [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, as the proportion of missing data increases, these imputation methods become increasingly more unreliable 16 . Outside the intensive care unit (ICU), ABGs are missing in over 75% of cases 17,18 . It is not surprising, therefore, that the only models that used the measured P/F ratio were derived in the ICU.…”
Section: Introductionmentioning
confidence: 99%